Correlation between Air Temperature and Humidity with the Presence of Aedes aegypti Larvae - Farida Heriyani (Berkala Kedokteran, 2019)
Abstract: Dengue Hemorrhagic Fever (DHF) is a disease that spread by mosquito type Aedes aegypti. The room condition for the water container, such as air temperature and humidity, are factors that influence the presence of Aedes aegypti larvae and whether those are favourable for breeding and their growth to be mature and act as DHF vector. This study aims to know the correlation between environmental factors of the location of the water container, assessed from room temperature and humidity with the presence of Aedes Aegypti larvae in elementary school in Banjarbaru Utara Regency. This is an observational analytic study. Samples obtained were rooms where water container was located in elementary schools in Banjarbaru Utara Regency. Data were then analysed using chi-square. The results are 19.2% rooms with optimum temperature and 85.9% rooms with optimum humidity for the growth of Aedes aegypti larvae. There were 39.1% water containers with no larvae, 12.2% were found few larvae, and 48.7% were found many larvae. From the analysis, there was no significant correlation between room temperature and the presence of Aedes larvae, yet there was found a correlation between air humidity and the presence of Aedes larvae in elementary school in Banjarbaru Utara area.